2013
DOI: 10.1002/adv.21368
|View full text |Cite
|
Sign up to set email alerts
|

Processing, Properties, and Applications of Polymer Nanocomposites Based on Layer Silicates: A Review

Abstract: The nanocomposites are materials, which involve fillers in the nanometer scale, yielding substantial improvements.Polymer-layered silicate nanocomposites have received much attention during the past decade and have great interest both in the academic field and in industry, since they often give more attractive improvement to material properties than both micro-and macrocomposite materials. This extensive review presents recent studies in polymer nanocomposites based on layered silicate. The background, morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 377 publications
(543 reference statements)
2
85
0
1
Order By: Relevance
“…Among them, organomodified layered clays resulted particularly attractive from a technological point of view for the production of polymeric nanocomposites with unique multifunctional properties. In fact, they are widespread available and cheap, can be delaminated into nanometric clay layers with high aspect-ratio into several matrices and provide the possibility of producing nanocomposite systems with tailored and balanced strength/stiffness/toughness and improved dimensional and thermal stability, fire retardancy and gas barrier characteristics, without detrimental effects on recyclability [4][5][6][7][8][9][10][11][12][13][14][15][16]. In addition, nanoparticles can be also used as synthetic fibers coating, in order to improve mechanical properties of interfaces in composite materials [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, organomodified layered clays resulted particularly attractive from a technological point of view for the production of polymeric nanocomposites with unique multifunctional properties. In fact, they are widespread available and cheap, can be delaminated into nanometric clay layers with high aspect-ratio into several matrices and provide the possibility of producing nanocomposite systems with tailored and balanced strength/stiffness/toughness and improved dimensional and thermal stability, fire retardancy and gas barrier characteristics, without detrimental effects on recyclability [4][5][6][7][8][9][10][11][12][13][14][15][16]. In addition, nanoparticles can be also used as synthetic fibers coating, in order to improve mechanical properties of interfaces in composite materials [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, various properties from the bulk material are introduced. The phenomenon of interphase formation is attributed to the plasticization of the polymer surfactants (Alateyah, Dhakal, & Zhang, 2013). Another explanation of the lower reduction of the T g value at a higher clay loading is the increased free volume of resin.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…[1][2][3] This clay has a laminar nanostructure that can delaminate during the mix processing. The dispersion of delaminated nanolayers and their strong interaction with the polymeric chains are essential conditions to improve the nanocomposite properties.…”
Section: Introductionmentioning
confidence: 99%
“…Processing conditions, the type of OMMT (basal spacing and organophilicity), and the use of compatibilizers are some of the crucial factors that have influences over the nanocomposite morphology. [2,3,7] Ardhyananta and Ismail [8] obtained EVA/OMMT nanocomposites by melt method and used ethylene glycol to compatibilize the polymer matrix-filler system. They concluded that the presence of the glycol polar groups increases the interaction between polymer chains (through vinyl acetate [VA] polar groups) and silicate surface.…”
Section: Introductionmentioning
confidence: 99%